PENGARUH PENGELOLAAN RISIKO DAN PERILAKU INOVATIF TERHADAP KEBERLANGSUNGAN USAHA UMKM YANG DIMODERASI OLEH KAPABILITAS JEJARING - Fitri Lukiastuti; Novi Riza Rosani (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2022)
The purpose of this study is to analyze the effect of risk management and innovative behaviour on MSME business sustainability and analyze the moderating role of network capabilities on the effect of risk management and innovative behaviour on MSME business sustainability. The research population is MSME business doers in the city of Semarang, amounting to 11,908 with a sample of 99 respondents calculated by random sampling technique. The quantitative data analysis using smart PLS with the stages of the outer model and inner model. The results of the study indicate that risk management and innovative behaviour have a positive significant effect on MSME business sustainability in the city of Semarang. Network capabilities strengthen the influence of risk management and innovative behaviour on MSME business sustainability in Semarang City.